Subjective Outcomes of Auditory Brainstem Implantation. Issue 5 (June 2015) - McSorley, Amanda; Freeman, Simon Richard Mackenzie; Ramsden, Richard Thomas; Motion, Jamie; King, Andrew Thomas; Rutherford, Scott Alexander; Mawman, Deborah Jane; O'Driscoll, Martin Paul; Lloyd, Simon Kingsley Wickham
Abstract : Aim: To assess the long-term subjective benefits of auditory brainstem implants (ABIs) and investigate the extent to which ABI users perceive it to be a useful device. Methods: Using the Manchester database, all 31 living patients registered as ABI users were identified and sent the ABI performance questionnaire. Data regarding daily duration of use, auditory fatigue, ability to differentiate between speech and environmental sounds, and subjective usefulness of the ABI in different listening conditions were collected. Patients were asked to rate the usefulness of the device in various settings on a scale of 1 (not useful) to 6 (very useful). The mean age at implantation was 33 years (13–73 yr), and the mean follow-up period was 6 years (1.5–15 yr). Results: Between March 1994 and September 2009, 57 patients underwent ABI insertion. A total of 26 patients were not eligible for inclusion in the study (19 nonusers, 5 deceased, and 2 sleepers). Of the 31 eligible patients identified as ABI users, 23 returned the questionnaire, 1 was excluded as the questionnaire had been completed on his or her behalf, giving a net response rate of 71%. Mean duration of usage per day was 12.62 hours (range, 8–16 h). Seventy-one percent of the patients turned the processor off at one or more points during the day. Differentiation between speech and environment was achieved in 95%, and 70% were able to differentiate between gender and adult and pediatric voices. The ABI was perceived as most beneficial when dealing with a familiar voice in a quiet place, with a median usefulness score of 4, rising to 5 when used in conjunction with lip reading. The ABI was least useful when dealing with an unfamiliar voice in a loud place, with a mean score of 1, rising to 2 when used in conjunction with lip reading. In all environments, combining the ABI with lip reading served to increase usefulness ratings by at least 1 point. Conclusion: This study demonstrates that ABI users make use of their device for at least 12 hours per day on average and obtain considerable subjective benefit in speech discrimination when using the device with familiar speakers in a quiet environment. Benefit is less significant in noise and with an unfamiliar speaker. Lip reading enhances subjective benefit by at least 1 point, and lip reading training may have a role to play in maximizing subjective benefit.